(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2020)
The CIES center “Centro de la Industria, la Empresa y los Servicios” (Center for Industry, Business and Services) of the SENA regional Norte de Santander is in charge of investing in the social and technical development ofColombian workers in comprehensive vocational training, with a wide range of resources of assets for your entire training line.A preventive maintenance plan was developed for equipment in the training environments for industrial mechanical maintenance, metalworking products, diesel engines, automotive electromechanical and diesel transmission mechanics. Said maintenance plan was developed as a first stage the characterization of the equipment, identification of these, collection of technical information, leading to the elaboration of technical sheets of all the equipment. As a second stage, the equipment was classified by its maintainability and criticality, classifying the maintainable, critical and non-critical equipment. As a third stage, an FMEA analysis of critical equipment was implemented. Thus, with the identification of the main failures and the recommended actions, the protocols and schedules of the selected assets were created.Once all this information was collected, formats for the equipment data record were created, necessary for the correct implementation of the preventive maintenance plan. Culminating with maintenance indicators to guarantee continuous improvement, thus increasing the reliability and availability of the equipment.